The outcomes of external dacryocystorhinostomy with bicanalicular silicone knot started in the lacrimal sac without suturing posterior flap - Genç, Selim; Ayyıldız, Taha; Şalkacı, Osman; Hassan, İbrahim Ali; Keinan, İbrahim Abdi; Çakır, Hanefi (The European Research Journal, 2021)
Objectives: During external dacryocystorhinostomy (DSR) - Bicanalicular silicone tube implantation (BSTI), it is aimed to utilize the mechanical pressure effect due to the initiation of silicone knotting inside the lacrimal sac and evaluate the effectiveness of this modified technique in which the sac and nasal mucosa posterior flaps are not sutured. Methods: Sixty-six patients between the ages of 8-57 years who were admitted to Kartal Lütfi Kırdar Training and Research Hospital and Somalia Mogadishu Recep Tayyip Erdogan Training and Research Hospital Eye Diseases outpatient clinic with irrigation and lacrimal secretion complaints between January 1, 2010 and December 31, 2019 were included in the study. In these patients with lacrimal stenosis, external dacryocystorhinostomy (DSR) and Bicanalicular silicone tube implantation surgery method were applied. Results: A total of 66 patients, 3 males (4.5%) and 63 females (95.5%), were included in this study. The mean age of the patients was 45 (8-57) years. It was determined that 4 of the patients who were followed up for an average of 16 months developed atrophic mucosa due to chronic rhinitis, and 6 developed nasolacrimal ductus obstruction due to excessive wound healing due to young age. Conclusions: When the comfort and complications it provides are evaluated together, this technique emerges as a preferred method.﻿